2007
DOI: 10.1074/mcp.m600464-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

The Serine/Threonine/Tyrosine Phosphoproteome of the Model Bacterium Bacillus subtilis

Abstract: Protein phosphorylation on serine, threonine, and tyrosine (Ser/Thr/Tyr) is well established as a key regulatory posttranslational modification in eukaryotes, but little is known about its extent and function in prokaryotes. Although protein kinases and phosphatases have been predicted and identified in a variety of bacterial species, classical biochemical approaches have so far revealed only a few substrate proteins and even fewer phosphorylation sites. Bacillus subtilis is a model Gram-positive bacterium in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
448
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 354 publications
(495 citation statements)
references
References 65 publications
27
448
7
Order By: Relevance
“…However, recent large scale genomic sequencing combined with the Global Ocean Sampling project (2) revealed that microbial eukaryotic-like protein kinases outnumber histidine kinases, traditionally considered the canonical microbial kinases (3). Likewise, our recent global and site-specific proteomics study of Ser/Thr/Tyr phosphorylation in Bacillus subtilis, a model Gram-positive bacterium, detected more than 100 phosphorylation events on 78 proteins, many of them classified as essential (4). Combined with previous two-dimensional gel studies using 32 P labeling (5-7), this strongly suggests that Ser/Thr/Tyr protein phosphorylation is common in bacterial cell, although at much lower levels than in its eukaryotic counterpart, and that it may be important in the regulation of bacterial cellular processes.…”
mentioning
confidence: 99%
“…However, recent large scale genomic sequencing combined with the Global Ocean Sampling project (2) revealed that microbial eukaryotic-like protein kinases outnumber histidine kinases, traditionally considered the canonical microbial kinases (3). Likewise, our recent global and site-specific proteomics study of Ser/Thr/Tyr phosphorylation in Bacillus subtilis, a model Gram-positive bacterium, detected more than 100 phosphorylation events on 78 proteins, many of them classified as essential (4). Combined with previous two-dimensional gel studies using 32 P labeling (5-7), this strongly suggests that Ser/Thr/Tyr protein phosphorylation is common in bacterial cell, although at much lower levels than in its eukaryotic counterpart, and that it may be important in the regulation of bacterial cellular processes.…”
mentioning
confidence: 99%
“…Evidence has accumulated confirming that S/T/Y phosphorylation is highly present in bacteria and has important regulatory roles [26-39, 41, 61]. Pioneering work by Macek and co-workers opened new avenues to identify hundreds of phosphorylation events in bacteria [14][15][16]. These studies led to important breakthroughs in the field of bacterial signalling, such as cross-talk between a S/T/Y kinase and a two-component H/D kinase found to be activated by YbdM-dependent phosphorylation [62].…”
Section: Discussionmentioning
confidence: 99%
“…Strong Cation Exchange (SCX) was performed as described elsewhere [14]. according to the manufacturer's protocol.…”
Section: Phosphopeptide Enrichmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Using colorimetric Pro-Q Diamond® (Invitrogen) staining, 32 P/ 33 P-radiolabeling or with the aid of phosphoprotein specific antibodies, phosphoproteins resolved on the 2-D gel can be revealed. 2-DE methods have been used to analyze the phosphoproteomes of several bacterial species, such as E. coli, Corynebacterium glutamicum, Neisseria meningitidis and B. subtilis (Cortay et al, 1986;Bendt et al, 2003;Macek et al, 2007;Bernardini et al, 2011). The phosphorylated proteins identified were involved in a variety of different cellular processes, such as central metabolism, with many having housekeeping functions.…”
Section: Post-translational Modifications (Ptms)mentioning
confidence: 99%